Immunogenic virus-like particles continuously expressed in mammalian cells as a veterinary rabies vaccine candidate - Fontana, Diego Sebastian (2015)
Rabies is one of the most lethal infectious diseases in the world, with a mortality approaching 100%. Thereare between 60,000 and 70,000 reported annual deaths, but this is probably an underestimation. Despitethe fact that there are vaccines available for rabies, there is a real need of developing more efficaciousand cheaper vaccines. This is particularly true for veterinary vaccines because dogs are still the mainvector for rabies transmission to human beings. In a previous work, we described the development andcharacterization of rabies virus-like particles (RV-VLPs) expressed in HEK293 cells. We showed that RV-VLPs are able to induce a specific antibodies response. In this work, we show that VLPs are able to protectmice against virus challenge. Furthermore, we developed a VLPs expressing HEK-293 clone (sP2E5) thatgrows in serum free medium (SFM) reaching high cell densities. sP2E5 was cultured in perfusion mode ina 5 L bioreactor for 20 days, and the RV-VLPs produced were capable of triggering a protective immuneresponse without the need of concentration or adjuvant addition. Further, these VLPs are able to inducethe production of rabies virus neutralizing antibodies. These results demonstrate that RV-VLPs are apromising rabies vaccine candidate.